ANALISIS RETROSPEKTIF INTEGRASI TEKNOLOGI DALAM DESAIN DIDAKTIS MATERI BANGUN RUANG SISI LENGKUNG UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Tri Nova Hasti Yunianta; Didi Suryadi; Rizky Rosjanuardi; Suhendra (Satya Widya, 2026)
The aim of this study is to examine the impact and potential of innovation and quality improvement in teaching curved-surface solid geometry for junior secondary school students. This study employs a qualitative approach using Didactical Design Research (DDR) to capture classroom realities, with retrospective analysis guiding the interpretation of findings. Data were collected through questionnaires, tests, documentation, in-depth interviews, and focus group discussions. The results show that students’ knowledge acquisition is supported by three key aspects: independent exploration, the use of technology, and a coherent learning trajectory. The implemented didactical design demonstrates several strengths but also areas for improvement. Technology effectively enhances concept visualization, student participation, and understanding. However, limitations remain in the clarity of task instructions, the precision of anticipating students’ learning obstacles, and the alignment of technology use with learning objectives. Reflection and evaluation of the implementation inform revisions to the didactical design, leading to a more effective, structured, and student-centered learning approach that better meets classroom needs.